Understanding the distinct role of PI3K(p110α) in cancer and the heart to prevent chemotherapy-induced cardiotoxicity: mechanisms and therapeutic opportunities - Teleah G. Belkin; Yow Keat Tham; Amanda J. Edgley; Julie R. McMullen (Frontiers in Cardiovascular Medicine, 2026)
The development of new cancer therapies with greater efficacy has reduced mortality for many cancers, as well as improving survivorship. However, for some cancer treatments, this has uncovered unintended cardiotoxicity during or after treatment, and cardiovascular disease has emerged as a leading cause of mortality in some cancer survivors. This may occur because many of the same growth factor signaling pathways that lead to tumor growth are also critical for maintaining normal heart function. A class IA phosphoinositide 3-kinase, PI3K(p110 α ), is a critical regulator of normal heart biology, function and exercise-induced cardiac protection, but is also mutated/increased in some cancer types. In this review, we discuss the dual role of PI3K(p110 α ) signaling in cancer and the heart. The paradox being, that inhibiting PI3K(p110 α ) in a setting of some cancer types would be beneficial for halting/slowing tumor progression but could also damage heart muscle cells. Exercise and PI3K(p110 α ) has beneficial effects on heart function via cardiac excitation and contraction, mitochondrial adaptations, cellular stress responses to promote survival, preventing cell death and cardiac fibrosis. We contrast this to the chemotherapy, doxorubicin, which is crucial for the treatment of many cancers but negatively impacts many of the beneficial effects of exercise and PI3K(p110 α ). Doxorubicin's clinical efficacy is limited by dose-dependent cardiotoxicity including cardiomyopathy, atrial fibrillation, and heart failure. A summary of reported cardiovascular effects in clinical trials using PI3K inhibitors is also provided. Finally, we discuss some of the current and emerging approaches to mitigate cancer therapy-induced cardiotoxicity including pharmacological interventions, gene therapy and dietary approaches based on preclinical studies. Advances in the field are likely to come from continued refinement of cardiotoxicity models, the investigation of targeting molecular pathways and targets with relevant primary endpoints for both cancer and heart function, and collaborative research with discovery/preclinical scientists and clinicians.